Identifikasi Elemen Fisik Ruang Publik yang Berpengaruh Terhadap Pembentukan Visual Kawasan Kota Tua Jakarta - Dedi Hantono; Abdul Hamid Hakim (EMARA: Indonesian Journal of Architecture, 2019)
The facade has become a major element in the formation of visual characters in an Old Jakarta area. But to improve the visual quality of the historic area, which is full of conserved buildings, changing the facade is one thing that is not permitted. Public space is the main alternative in improving the visual quality of the Jakarta Old Town area. This study aims to identify the physical elements that have an influence on the visual formation of the Jakarta Old Town area. Data were collected using a questionnaire for 10 respondents. By using a regression test, the relationship between variables was tested to investigate the effect between variables, and analyzed with a post positivistic approach. The results show that public space that affects the visual quality of Jakarta's Old City are four elements with linear formation; including roads, streams and pedestrian paths; and one square element (shared space)